"Flatten the Curve": Data-Driven Projections and the Journalistic Brokering of Knowledge during the COVID-19 Crisis. Issue 9 (21st October 2021) - Pentzold, Christian; Fechner, Denise J.; Zuber, Conrad
Abstract: The Coronavirus has prompted an urgent need for guidance and practical intervention. Newsmakers responded to this demand by providing outlooks that plotted the contagion's contours against a host of parameters. The article looks back at this acute area of sensemaking where journalistic forecasts, epidemiological modelling, and policy measures intertwined. It examines how possible courses of the pandemic were displayed and discussed in the multimodal infographics and reports of data journalistic news products. The estimations predominantly choose to take the form of bell-shaped curves which conceived of the disease as a kind of wave that should, after reaching its peak, flatten out again. Confronted with an immense degree of uncertainty around the illness and an ambiguous environment of conflicting meanings and explanations, we argue that this predictive newswork fulfilled some of the journalistic functions of brokering knowledge. By giving cogent visual form to the incoherent prognoses, it raised awareness of the available models and rendered COVID-19's potential developments accessible to policy makers and the public. By comparing sources, the data-driven forecasts fostered engagement with the spectrum of outlooks and the uncertainty they entailed. Furthermore, the news pieces connected consonant sources from science and public health institutions.